Economic analysis of biodiesel production from waste cooking oil. Issue 10 (3rd October 2017) - Avinash, A.; Murugesan, A.
ABSTRACT: Renewable diesel fuel or biodiesel is one of the prospective growth inducers that could help to resolve a country's economic problem and will decrease the nation's dependence on foreign energy imports. In this context, an economic evaluation of biodiesel production from waste cooking oil is reported in this study. The biodiesel was produced from waste cooking oil by transesterification process. The by-product glycerol produced during transesterification is purified and recovered for its commercial value. Also, unreacted methanol after transesterification is recovered by distillation and recycled for reuse. The biodiesel production facility developed in this study is dedicated to the production of 39, 208 metric tons of biodiesel per year. The total capital investment charged to this project is estimated to be Rs. 1, 615, 133, 000. At a value of Rs. 15/kg for feedstock waste cooking oil, a biodiesel cost of Rs. 55/kg was estimated. Along with main revenue from biodiesel, additional revenue of around Rs. 22/kg can be generated from the sale of glycerol. On the whole, the profitability analysis of the study discloses that the modeled biodiesel production plant has the ability to produce biodiesel with unit production cost of Rs. 51/kg and unit production revenue of Rs. 58/kg.